2004
DOI: 10.1787/jbcma-v2004-art10-en
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Sentiment and Economic Activity

Abstract: The objective of this article is to reassess the validity of the consumer confidence (or sentiment) indices in anticipating the evolution of economic activity by considering a fairly high number of countries across the world (i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(54 citation statements)
references
References 33 publications
2
49
0
3
Order By: Relevance
“…Blanchard concluded that the consumption shock at least to some extent was caused by "animal spirits". Other VAR-based papers that subscribes to the "sentiments" view on confidence shocks include Fuhrer (1993), Farmer and Guo (1994), Matsusaka and Sbordone (1995), Chauvet and Guo (2003), Golinelli and Parigi (2004) and Ling et al (2015).…”
Section: A Brief Review Of Related Literaturementioning
confidence: 99%
“…Blanchard concluded that the consumption shock at least to some extent was caused by "animal spirits". Other VAR-based papers that subscribes to the "sentiments" view on confidence shocks include Fuhrer (1993), Farmer and Guo (1994), Matsusaka and Sbordone (1995), Chauvet and Guo (2003), Golinelli and Parigi (2004) and Ling et al (2015).…”
Section: A Brief Review Of Related Literaturementioning
confidence: 99%
“…The availability by country of such indicators is uneven: the services production index (including trade, transport and communication) is available only for Canada and Japan, while for the remaining G7 countries it is only possible to use some demand-side proxies, such as the consumption of manufactured goods (for France and Japan) and the retail sales index. Alternatively, the production of services may be proxied either by general indicators, such as survey indexes on trade and on the consumer sentiment (see Golinelli and Parigi, 2004), or by labour market indicators.…”
mentioning
confidence: 99%
“…Some authors have already empirically enquired into the interpretation of the sentiment index: for instance, Locarno and Parigi (1997) found that Italian CSI was significantly explained by socio-economic factors, providing first evidence supporting the original Katona's view. More recently, in a study on eight countries over about thirty years, Golinelli and Parigi (2004) confirm that sentiment is driven by economic as well other factors, but they found that this correlation is not homogenous across countries and may also change over time 14 . Starting from these considerations, we firstly estimate a model including only macroeconomic variables that may be considered to influence household behaviour (eq.…”
Section: Interpreting the Isae Consumer Sentiment Indicatormentioning
confidence: 97%
“…ISAE (formerly ISCO) realises the survey for Italy since 1973, at the beginning on a quarterly basis and then monthly since 1982. Survey results are often employed to provide short-term forecasts (Parigi and Schlitzer, 1997;Carnazza and Parigi, 2001) and for cyclical analysis (Bovi et al 2000;Parigi, 2004 and. Some authors have also already enquired into the theoretical interpretation of the Italian Consumer Sentiment Index (CSI), finding somewhat mixed results (Locarno and Parigi, 1997).…”
Section: Movente Psicologico Fiducia E Spesa Per Consumi: Un'analisimentioning
confidence: 99%